Assessing Teachers' Capabilities to Work with Models and Evaluate Results in the Context of a Complex and Authentic STEM Problem - André Greubel; Hans-Stefan Siller; Martin Hennecke (MDPI AG, 2024)
Since the practice turn, the contemporary education landscape has been shifting from mere knowledge dissemination to empowering students to solve problems. Special emphasis is given to problems on which students work for an extended period (at least several hours; frequently multiple school days). While working on such problems, it is essential to employ a variety of activities. Two of these are working with models and evaluating models and their results. One topic that has received little attention up to now is the question of to what extent educators are able to apply these skills. This study, fundamentally exploratory in nature, seeks to delve into such an assessment by evaluating the competence of <semantics>n=20</semantics> educators in estimating and evaluating building evacuation duration using digital simulations. Our results show that the participants self-assessed as being able to solve such exercises. However, this was contrasted by our external assessment of the solutions provided by the participants, which showed that the solutions lacked in quality.